Force.com enterprise architecture : blend industry best practices to architect and deliver packaged Force.com applications that cater to enterprise business needs /: blend industry best practices to architect and deliver packaged Force.com applications that cater to enterprise business needs. (2014) - Fawcett, Andrew
No abstract available